Foreign direct investment and economic growth relationship in Croatia - Vlatka Bilas (UTMS Journal of Economics, 2019)
It is often stated that foreign direct investment (FDI) influence positively economic growth of the host country, but empirical evidences are still heterogenous. The paper examines the relationship between the FDI and economic growth (real GDP) in Croatia for the period 1995-2018. The research data were retrieved from the World Bank database. Two options of time series were considered: (1) real GDP growth rate and logarithm of FDI and (2) real GDP growth rate and logarithm of FDI/GDP. In order to examine the relationship between FDI and real GDP different cointegration tests were employed, as well as Granger causality analysis for both options. Based on the conducted analysis following conclusions can be made: (1) results of the cointegration tests indicated that there is no long-run equilibrium relationship between real GDP growth rate and any of the foreign direct investment series; (2) results of Granger causality tests indicated that there is no causal relationship between real GDP growth rate and any of the foreign direct investment series. In other words, foreign direct investments have no statistically significant impact on the growth rate of the real GDP in Croatia for the period being investigated.
Keywords: F21; F43; 330; cointegration; Granger causality